Curriculum Evaluation Islamic Religious In Al-Barokah Elementary School - Al-Ghifary, Dwi Fikry; Erihadiana, Mohammad; Siregar, Hariman Surya (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2023)
This research aims to determine the PAI curriculum evaluation model used at SD Al-Barokah Bandung. This research is motivated by the urgency to assess success in education. So curriculum evaluation becomes an important part implemented continuously as a basis for controlling the effectiveness and efficiency carried out to perfect the curriculum. This research uses a qualitative approach using analytical descriptive methods and is included in field research. Data collection was carried out using triangulation techniques, combining interviews, observations, and documentation studies. The results of all the data in this research are then analyzed, consisting of reduction, display, and verification of the data so that conclusions can be drawn. The results of his research at Al-Barokah Elementary School have carried out regular evaluations of the PAI curriculum, namely at the beginning of each school year. PAI teachers carry out evaluations approaching the CIPP evaluation model where what is evaluated is context, input, process, and product.